Shrinkage and Absorption of Sand Concrete Containing Marble Waste Powder - Djebien, Rachid; Abbas, Yassine; Bouabaz, Amel; Ziada, Yasser Nacereddine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the context of growing scarcity of natural resources, the high demand of aggregates and the difficulties to open new quarries, several studies were carried out to study the possibility of reuse of waste and industrial by-products to replace traditional materials which would run out, replace materials when transport distances increase to reduce construction costs and protect the environment.
Keywords: sand concrete; marble powder; waste; shrinkage; absorption; kruszywo betonowe; proszek marmurowy; odpady; wchłanianie